Peritoneal Dialysis Catheters to Treat Refractory Non-Malignant Ascites. Issue 4 (July 2017) - Hingwala, Jay; Whitlock, Reid; Dunsmore, Sara; Armstrong, Sean; Tangri, Navdeep; Komenda, Paul
Refractory non-malignant ascites is associated with significant morbidity. Serial, large-volume paracentesis is a common treatment. Tunneled peritoneal dialysis (PD) catheters are an effective treatment for refractory malignant ascites, but there are limited data on complications and effectiveness for non-malignant ascites. We reviewed all 13 PD catheter insertions between 2010 - 2015 for this indication at our center. The median catheter survival time was 146 days. No complications occurred during catheter insertion, and no mechanical complications occurred after catheter insertion. One case of peritonitis developed over 217 catheter months. Peritoneal dialysis catheters may be a safe and effective option to manage refractory non-malignant ascites. Prospective, randomized trials are needed to better evaluate potential risks and benefits.